To Hell, with Shakespeare - Lee, Ei Leen * (Elsevier, 2010)
In the teaching of Shakespearean plays to ESL students, deciphering Shakespeare‟s language has often been cited as the main obstacle to comprehending his work. While this may hold true to a large extent, there are other „aspects‟/‟areas‟ in Shakespeare‟s plays such as the concept of Hell and black comedy, which may prove equally demanding to comprehend in the ESL classroom. Humor is not only relative but it is also time and culture-bound; in the case of the Malaysian classroom, getting students from different ethnic and religious backgrounds to comprehend the black humor in the Porter‟s scene in Macbeth is no laughing matter. This paper reports on how the researcher tapped on the diverse religious beliefs of the students and used Taoist, Muslim, and Hindu concepts of the afterlife as a prelude to teach and read the Porter‟s scene. Following this, the ESL students engaged in communicative, language-based activities such as interviews with the Porter or characters in the afterlife to suspend disbelief and transcend the text. As a result of the creative methodology used in the class, the ESL students were able to discuss and comprehend Shakespeare‟s treatment of Hell and grasp the concept of black comedy in the play. In conclusion, the methodology advocated in the study celebrated creativity and diversity in the Malaysian classroom.